Let $g: [0, \pi]\rightarrow \mathbb{R}$ a $C^{\infty}$ function for which the following stands: $$g(0)=0 \ \ , \ \ g(\pi)=0$$

I have to show that $$\int_0^{\pi}g^2(x)dx \leq \int_0^{\pi}(g'(x))^2dx$$ using Parseval's formula.


I have done the following:

The Fourier series of $g$ is $$g \sim \frac{a_0}{2}+\sum_{k=1}^{\infty}\left (a_k \cos (kx)+b_k \sin (kx)\right )$$ where $$a_0=\frac{2}{\pi}\int_0^{\pi}g(x)dx \\ a_k=\frac{2}{\pi}\int_0^{\pi}g(x)\cos (kx)dx \ \ , \ \ k=1, 2, \dots \\ b_k=\frac{2}{\pi}\int_0^{\pi}g(x)\sin (kx)dx \ \ , \ \ k=1, 2, \dots $$

From Parseval's formula we have the following:

$$\int_0^{\pi}\left (\frac{a_0}{2}\right )^2dx+\sum_{k=1}^{\infty}\left (a_k^2\int_0^{\pi}\cos^2 (kx)dx+b_k^2\int_0^{\pi}\sin^2 (kx)dx\right )=\int_0^{\pi}g^2(x)dx \\ \Rightarrow \int_0^{\pi}g^2(x)dx=\frac{a_0^2}{4}\pi+\frac{\pi}{2}\sum_{k=1}^{\infty}\left (a_k^2+b_k^2\right )$$

The Fourier series of $g'$ is $$g'\sim \sum_{k=1}^{\infty}\left (kb_k\cos (kx)-ka_k\sin (kx)\right )$$

From Parseval's formula we have the following:

$$\sum_{k=1}^{\infty}\left (k^2b_k^2\int_0^{\pi}\cos^2 (kx)dx+(-k)^2a_k^2\int_0^{\pi}\sin^2 (kx)dx\right )=\int_0^{\pi}(g'(x))^2dx \\ \Rightarrow \int_0^{\pi}(g'(x))^2dx=\frac{\pi}{2}\sum_{k=1}^{\infty}\left (k^2b_k^2+k^2a_k^2\right )$$

Is this correct?? Or have I done something wrong at the application of Parseval's formula??

How could I continue to show the inequality $$\int_0^{\pi}g^2(x)dx \leq \int_0^{\pi}(g'(x))^2dx$$ ??




When we have to show with the Parseval's formula an inequality in which case do we have to take an expansion of the function that is involved at the inequality??

  • $\begingroup$ Well, I have the impression that you integral of $g'^2$ could be negative. The reason is that that minus should not be there, since it gets squared with the coefficients. With that, your inequality becomes $\sum(k^2-1)(b_k^2+a_k^2)\geq\frac{a_0^2}{2}$, by carrying the LHS to the right except for the $a_0$ term, putting sums together and dividing both sides by $\frac{\pi}{2}$. Can you show it holds regardless of the coefficients? $\endgroup$ – MickG May 9 '15 at 16:14
  • $\begingroup$ I edited my initial post... I changed the sign... Is it correct now?? @MickG $\endgroup$ – Mary Star May 9 '15 at 16:18
  • $\begingroup$ Yes, I think the post is now correct. As I said, if you carry the LHS sum over to the right and put it together with the one on the RHS and then divide by pi/2, you get an inequality which seems pretty obvious, but can you prove it? I'm not too sure I can… $\endgroup$ – MickG May 9 '15 at 16:21
  • $\begingroup$ @MickG I have the following idea: $\endgroup$ – Mary Star May 9 '15 at 16:50
  • $\begingroup$ $$\sum_{k=1}^{\infty}(k^2-1)(b_k^2+a_k^2)\geq \frac{a_0^2}{2} \\ \Rightarrow \sum_{k=1}^{\infty}(k^2-1)(\frac{4}{\pi^2}\int_0^{\pi}g^2(x)\sin^2 (kx)dx+\frac{4}{\pi^2}\int_0^{\pi}g^2(x)\cos^2 (kx)dx)\geq \frac{\frac{4}{\pi^2}\int_0^{\pi}g^2(x)dx}{2} \\ \Rightarrow \sum_{k=1}^{\infty}(k^2-1)\frac{4}{\pi^2}\int_0^{\pi}g^2(x)(\sin^2(kx)+\cos^2(kx))dx\geq \frac{\frac{4}{\pi^2}\int_0^{\pi}g^2(x)dx}{2}\\ \Rightarrow \sum_{k=1}^{\infty}(k^2-1)\frac{4}{\pi^2}\int_0^{\pi}g^2 (x)dx \geq \frac{\frac{4}{\pi^2}\int_0^{\pi}g^2(x)dx}{2}\\ \Rightarrow \sum_{k=1}^{\infty}2(k^2-1) \geq 0 \text{ which is true.}$$ $\endgroup$ – Mary Star May 9 '15 at 16:50

Suppose g is absolutely continuous in $[0, \pi]$ and $g(0) = 0$. Suppose further that $g ‘$ is square integrable. Take the half sine series of g, that is to say we extend g to an odd function G in $[ - \pi , \pi ]$. Then G is periodic, absolutely continuous of period $ 2 \pi $ and the derivative $ G’ $ is Lebesgue integrable and square integrable since $ g ‘$ is square integrable.
The next thing we need to use is the relation between the Fourier coefficients of $G$ and the Fourier coefficients of $ G ‘$.
If (0, bn ) is the Fourier series of $ G $ , then ( n bn , 0) is the Fourier coefficients of $ G’ $. More precisely the formal derived series of the Fourier series of G is the Fourier series of $ G ‘$. Now we can invoke Parseval Theorem, since $ G $ and $ G’ $ are square integrable, to get:

$\frac{1}{\pi }\int_{ - \pi }^\pi {{G^2}(x)dx = \sum\limits_{n = 1}^\infty {b_n^2} } $ and

$\frac{1}{\pi }\int_{ - \pi }^\pi {{{(G'(x))}^2}dx} = \sum\limits_{n = 1}^\infty {{n^2}b_n^2} $.


$\frac{2}{\pi }\int_0^\pi {{g^2}(x)dx = \sum\limits_{n = 1}^\infty {b_n^2} } \le \sum\limits_{n = 1}^\infty {{n^2}b_n^2} = \frac{1}{\pi }\int_{ - \pi }^\pi {{{(G')}^2}(x)dx} = \frac{2}{\pi }\int_0^\pi {{{(g')}^2}(x)dx} $

and $\int_0^\pi {{g^2}(x)dx} \le \int_0^\pi {{{(g'(x))}^2}dx} .$

The key to this problem is square integrability and the condition to extend to a continuous periodic odd function. g being absolutely continuous means that its derived function is Lebesgue integrable but may not be square integrable so we make the assumption that $ g' $ is square integrable. If g is smooth then both g and $g'$ are continuous and so are both square integrable. For the extension to odd continuous function we just need to have $g(0) = 0$. We do not need to expand the function as a Fourier series. We do not need to use the convergence of the Fourier series.


Let $G:[-\pi,\pi] \to \mathbb{R}$ be defined by $$ G(x) = \begin{cases} g(x) & \text{if } 0 \le x \le \pi \\ -g(-x) & \text{if } -\pi \le x < 0 \end{cases} $$ You can check that this function is continuous and differentiable (this is where the fact that $g(0) = 0$ is needed). Its derivative is given by $$ G'(x) = \begin{cases} g'(x) & \text{if } 0 \le x \le \pi \\ g'(-x) & \text{if } -\pi \le x < 0 \end{cases} $$ Notice that $G'$ is continuous since $g$ is $C^\infty$.

Because $G$ is odd and $G'$ is even, their Fourier series have the following form : \begin{align} G &\sim \sum_{k=1}^\infty b_k \sin(kx) \\ G' &\sim \sum_{k=1}^\infty A_k \cos(kx) \end{align} Using integration by parts and the fact that $G(\pi) = G(-\pi) = 0$, we can show that $A_k = k b_k$ : \begin{align*} A_k &= \frac{1}{\pi} \int_{-\pi}^\pi G'(x)\cos(kx) \,dx \\ &= \frac{1}{\pi}\left[ G(x)\cos(kx) \right]_{x=-\pi}^{x=\pi} - \frac{1}{\pi} \int_{-\pi}^\pi G(x)(-k\sin(kx)) \,dx \\ &= k\frac{1}{\pi} \int_{-\pi}^\pi G(x)\sin(kx) \,dx \\ &= k b_k \end{align*}

Since $G$ and $G'$ are both continuous and $2\pi$-periodic, we can now use Parseval's formula to conclude the proof : \begin{align*} \int_0^\pi g(x)^2 \,dx &= \frac{1}{2} \int_{-\pi}^\pi G(x)^2 \,dx \\ &= \frac{\pi}{2} \sum_{k=1}^\infty b_k^2 \\ &\le \frac{\pi}{2} \sum_{k=1}^\infty k^2 b_k^2 \\ &= \frac{1}{2} \int_{-\pi}^\pi G'(x)^2 \,dx \\ &= \int_0^\pi g'(x)^2 \,dx \end{align*}

  • $\begingroup$ Just to add that G is continuous in $[- \pi, \pi]$ since $g(0) = g( \pi) $ . Then the differentiated series is automatically the Fourier series of $G '$ . [On account of the Fundamental Theorem of Calculus, the constant term of the Fourier series of G' is 0 bec of $g(0) = g( \pi)$ by integrating $G'$ and use FTC.] You have essentially proved this. $\endgroup$ – user231543 May 10 '15 at 7:59
  • $\begingroup$ This result holds for general $g$ if $g(0) = g( \pi) $, $g$ is absolutely continuous (so we have the Fundamental Theorem of Calculus) and $g'$ is square integrable. [If g is smooth, then it is absolutely continuous and $g'$ is integrable and square integrable . ] The proof is exactly as you have indicated $\endgroup$ – user231543 May 10 '15 at 8:01
  • $\begingroup$ I missed out that g must also satisfied g(0) = 0 so that the extension of g to G is continuous in $[-\pi, \pi]$ $\endgroup$ – user231543 May 10 '15 at 8:21
  • $\begingroup$ I see... Thank you very much!! :-) $\endgroup$ – Mary Star May 10 '15 at 15:57
  • $\begingroup$ When we have to show with the Parseval's formula an inequality in which case do we have to take an expansion of the function that is involved at the inequality?? @Math536 $\endgroup$ – Mary Star Jun 15 '15 at 18:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.